Structural information and communication complexity : 23rd International Colloquium, SIROCCO 2016, Helsinki, Finland, July 19-21, 2016, Revised selected papers /: 23rd International Colloquium, SIROCCO 2016, Helsinki, Finland, July 19-21, 2016, Revised selected papers. (2016) - Unknown
No abstract available